Acadêmico idoso no ensino superior: características de altas habilidades/superdotação? - Costa, Leandra Costa da (2012)
The objective of this is to discuss the continuity from old learners from research High Skills/ Giftedness characteristics (HS/G) in elderly scholars entered in higher education at Universidade Federal de Santa Maria and thus relate to matters of common sense about this age group as the idea that old age is directly related to the economic downturn of life in society. Justified the necessity and importance of this work because there are no studies regarding High skills/Giftedness related to elderly. The methodological option for this study was the qualitative approach and data collection was carried out through an interview structured way. Data analysis was developed in a proposal from content analysis, with the production of three frames that expose the narratives of senior academics inserted in Higher Education from UFSM, enabling the relationship with the features of the High Skills/Giftedness: above average skill, involvement with the task and creativity. The subjects of this research were 5 students which are more than 60 years, and they had vestibular in face mode in order to entry at UFSM, and now they regular students from the institution. Human beings requires that his areas of interest are recognized, being present in your daily life, motivation and incentives needed for challenges, regardless of their age, is always seeking something that leads to personal fulfillment. Thus, this study intends to insert the this population into the research line of High Sills/Giftedness.